Investigating the Effect of E-Book Utilization on Students’ Comprehension and Reading Interest at SMAN 01 Sukau - Apiana, Pia; Syamsiah, Nur; Suryawati, Sri Suci (Universitas Pamulang, 2026)
This research investigates the influence of e-book utilization on students’ reading comprehension and reading interest at SMAN 01 Sukau, motivated by the growing shift toward digital learning and the persistent low reading interest in Indonesia. Employing a quantitative design, the study involved 24 students who completed questionnaires supported by observation and document analysis. The results show that e-books have become a regular part of students’ reading routines, with most respondents reading e-books once a week. Although printed books remain the preferred format for 41.7% of students, the majority acknowledged the convenience, accessibility, and customizable features of e-books. Over half of the students reported that their comprehension and retention when using e-books were comparable to printed books, while 41.7% experienced improved understanding with digital formats. E-books also positively affected students’ reading motivation, with 75% stating that they spent the same or more time reading digitally and over half reporting increased interest due to features such as instant access to materials and environmentally friendly benefits. Nonetheless, several challenges were identified, including limited annotation tools, difficulty concentrating on screens, navigation issues, and occasional technical constraints. Overall, the findings indicate that e-books offer practical learning advantages and can enhance reading engagement, though improvements in digital literacy and e-book usability are necessary to optimize their effectiveness. This study contributes to understanding how digital reading tools support learning in Indonesian high schools and highlights the need for strategies that address both motivational and technological barriers in digital reading environments.